Pendidikan dan Pelatihan Pencegahan Penyakit Jaringan Periodontal pada Guru dan Orang Tua SDN Tomang 01 - Komala, Olivia Nauli; Astoeti, Tri Erri; Binartha, Ciptadhi Trioka; Panjaitan, Caesary Cloudya; Nasution, Fajar Hamonangan (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Periodontal disease is one of the diseases with a high prevalence in Indonesia. The cause of periodontal disease is inadequate oral hygiene and is also exacerbated by crowded teeth. Preventive measures include using an appropriate toothbrush, using interdental cleaners to clean between teeth, and getting orthodontic treatment if teeth are crowded. Parents have a responsibility towards the health of their children. Parents can influence their children's oral health by their dental health knowledge, habits, and behaviors. Teachers also play a role in improving the dental and oral health of elementary school students. The education and training that were carried out aimed to increase the knowledge of parents and teachers regarding periodontal disease. These activities were held at SDN Tomang 01 with teachers and parents on Tuesday, May 7, 2024 at 10.00-12.00. There were 27 participants in attendance. The education covered topics such as the healthy periodontal tissue, different types of periodontal disease, the causes behind it, as well as its treatment and preventative methods. The training encompassed instructions on proper tooth brushing techniques, as well as guidance on the utilization of dental floss and interdental brushes. Questions and answers were conducted after education. Knowledge improvement is evaluated by providing pre-tests and post-tests before and after education and training. The pre-test and post-test assessments revealed a significant improvement in the accuracy of answers, with the right response value increasing from 40 (16.330) to 60 (14.720). By implementing these activities, it is anticipated that periodontal disease can be averted.